Ventilation and perfusion scintigraphy after lung transplantation - E. V. Migunova; Е. А. Tarabrin; N. E. Kudryashova; O. G. Sinyakova; N. A. Karchevskaya; A. G. Petukhova; A. A. Saprin; T. E. Kallagov (Трансплантология (Москва))
Study objective. Evaluation of the possibilities of ventilation and perfusion scintigraphy in detecting functional disorders and determining the severity of lung damage that may occur after organ transplantation. Material and methods. The study included 27 patients after bilateral lung transplantation; mucoviscidosis was the main cause of terminal respiratory failure in most cases (19 patients; 77.8%). The ventilation scintigraphy was performed with 99mTc-pentatech using a nebulizer, and the perfusion scintigraphy was performed with 99mТс-albumin macroaggregate. The investigations were performed on Infinia II and Discovery 670 NM/CT single-photon emission tomographs (GE, USA). Results. Changes in the quantitative parameters of ventilation and perfusion scintigraphy in patients after lung transplantation were studied. When analyzing the results of radionuclide studies, we identified a restoration of function after lung transplantation, and the appearance of disorders with the development of complications in the early (up to 4 months) and later (more than one year) periods after bilateral lung transplantation. Conclusion. The study has shown that the radionuclide method has wide possibilities for assessing the ventilation and perfusion functions in patients after lung transplantation, helping in the differential diagnosis of obliterating bronchiolitis and graft vascular sclerosis, in assessing the nature of alveolar-capillary diffusion disorders, and determining the extent of functional abnormalities in every individual patient. Monitoring the function of transplanted lungs using scintigraphy allows separate monitoring of ventilation and perfusion changes, which is important for the choice of treatment tactics.